2021
DOI: 10.3389/fpsyt.2021.537137
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Colorectal Cancer in Patients With Attention-Deficit Hyperactivity Disorder: A Nationwide, Population-Based Cohort Study

Abstract: Background: The association between attention-deficit hypersensitivity disorder (ADHD) and the risk of developing colorectal cancer (CRC) is, as yet, to be investigated, and thus, we have conducted this nationwide, cohort study to examine the association in patients from Taiwan.Methods: In this study, 798 individuals with newly diagnosed ADHD and 2,394 (1:3) age-, gender-, and index year- matched controls without ADHD were enrolled, between 2000 and 2013, from the Longitudinal Health Insurance Database, a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Although the study of the relationship between cancer and ADHD is still in its infancy, there are recent interesting studies linking both pathologies. For instance, a retrospective cohort study carried out in Taiwan reported that ADHD was associated with an increased risk of colorectal cancer (adjusted Hazard Ratio = 3.458, 95% CI = 1.640–7.293, p < 0.001) [ 77 ]. Furthermore, a history of a neurodevelopmental disorder (ADHD, autism spectrum disorder, and intellectual disabilities) was associated with an increased risk of seminoma) in a nested case-control study (OR: 1.54; 1.09–2.19 [ 78 ].…”
Section: Speer Allergic Tension-fatigue Syndrome (Satfs) Re-visitedmentioning
confidence: 99%
“…Although the study of the relationship between cancer and ADHD is still in its infancy, there are recent interesting studies linking both pathologies. For instance, a retrospective cohort study carried out in Taiwan reported that ADHD was associated with an increased risk of colorectal cancer (adjusted Hazard Ratio = 3.458, 95% CI = 1.640–7.293, p < 0.001) [ 77 ]. Furthermore, a history of a neurodevelopmental disorder (ADHD, autism spectrum disorder, and intellectual disabilities) was associated with an increased risk of seminoma) in a nested case-control study (OR: 1.54; 1.09–2.19 [ 78 ].…”
Section: Speer Allergic Tension-fatigue Syndrome (Satfs) Re-visitedmentioning
confidence: 99%
“…Existing observational studies have established associations between mental disorders and various types of cancers. For example, ADHD is correlated with an increased risk of colorectal cancer [3], while AN is implicated in elevated risk for both lung cancer and esophageal cancer [4], as well as a reduced risk of breast cancer [5]. BD appears to be associated with an increased risk of multiple types of cancers, particularly breast cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%